The Role of Madrasah Principal Leadership in Developing Students’ Social Character at MTsN 4 Mandailing Natal - M Yassir Ridho; Amiruddin Siahaan; Neliwati Neliwati (Journal of General Education and Humanities, 2025)
This study investigates the role of the madrasah principal’s leadership in shaping students’ social character at MTsN 4 Mandailing Natal. The research addresses the problem of how leadership practices influence the development of core social values in students, aiming to explore the strategies and impacts of principal-led character education. Using a qualitative approach, data were collected through in-depth interviews, direct observations, and analysis of school documents. The findings highlight the principal’s role as a role model, policy maker, and facilitator in embedding Islamic values across educational practices. Key social character traits, politeness, responsibility, discipline, compassion, and cooperation—are nurtured through religious activities, student empowerment, and collective engagement within a spiritually enriched school culture. This research contributes to understanding leadership-based character education and offers practical implications for educational leaders in Islamic contexts.